Modern sea-level rise breaks 4,000-year stability in southeastern China - Yucheng Lin; Robert E. Kopp; Haixian Xiong; Fiona D. Hibbert; Zhuo Zheng; Fengling Yu; Praveen Kumar; Sönke Dangendorf; Hailin Yi; Yaze Zhang (Nature, 2025)
Abstract Quantifying physical mechanisms driving sea-level change—including global mean sea level (GMSL) and regional-to-local components (that is, sea-level budget)—is essential for reliable future projections and effective coastal management 1,2 . Although previous research has attempted to resolve China’s sea-level budget from the 1950s 3,4 , these studies capture short timescales and lack the long-term context necessary to fully assess modern sea-level rise in southeastern China 5 —one of the world’s most densely populated regions with immense socioeconomic importance 6 . Here we show that GMSL followed three distinct stages from 11,700 years before present (BP) to the modern day: (1) rapid early Holocene rise driven by the deglacial melt of land ice; (2) 4,000 years of stability from around 4200 BP to the mid-nineteenth century when regional processes dominated sea-level change; and (3) accelerating rise from the mid-nineteenth century. Our results arise from spatiotemporal hierarchical modelling of geological sea-level proxies and tide gauge data to produce site-specific sea-level budget estimates with uncertainty quantification. It is extremely likely ( P ≥ 0.95) that the GMSL rise rate since 1900 (1.51 ± 0.16 mm year −1 , 1 σ ) has exceeded any century over at least the past four millennia. Moreover, our analysis indicates that at least 94% of rapid modern urban subsidence is attributable to anthropogenic activities, with localized subsidence rates often exceeding GMSL rise. Such concurrent acceleration of global sea-level rise and rapid localized subsidence has not been observed in our Holocene geological record.